Effect of Marketing mix on BNI Syari’ah Bengkulu Customer Loyalty - Nurma Diana; Yulius Wahyu Setiadi (Journal of Indonesian Management, 2021)
This study aims to determine the effect of the service marketing mix on customer loyalty studies at BNI Syari'ah and to determine the effect of 7P (product, price, place, promotion, people, physical evidence, and process) on customer loyalty BNI Syari'ah. This type of research uses a quantitative approach. The population used in this study were all customers of BNI Syariah Bank and the sampling in this study was accidental sampling, the data analysis technique was multiple linear regression. Product (X1) has a positive and significant effect on BNI Syari'ah Customer Loyalty (Y). This is evidenced by the results of the t test which shows tcount > ttable (2.159 > 1.98137) and (sig < = 0.043 < 0.050). Price (X2) has a positive and significant effect on BNI Syari'ah Customer Loyalty (Y). This is evidenced by the results of the t test which shows tcount > ttable (2.526 > 1.98137) and (sig < = 0.013 < 0.050). Location (X3) has a positive and significant effect on BNI Syari'ah Customer Loyalty (Y). This is evidenced by the results of the t test which shows tcount > ttable (2.548 > 1.98137) and (sig < = 0.012 < 0.050). Promotion (X4) has a positive and significant effect on BNI Syari'ah Customer Loyalty (Y). This is evidenced by the results of the t test which shows tcount > ttable ( 14,689 > 1.98137) and (sig < = 0.000 < 0.050). Employees (X5) have a positive and significant effect on BNI Syari'ah Customer Loyalty (Y). This is evidenced by the results of the t test which shows tcount > ttable (2.634 > 1.98137) and (sig < = 0.027 < 0.050).